Dragon age: wraiths of tevinter ebook - DeFilippis, Nunzio (Dragon Age., 2022)
The trilogy that pits Fenris and the Inquisition against the Venatori for the fate of Thedas collected in a deluxe edition. BioWare's award-winning game of the year dark fantasy RPG Dragon Age: Inquisition gets a canonical continuation in this collection of Dragon Age: Deception, Dragon Age: Blue Wraith, and Dragon Age: Dark Fortress.